FAKTOR RISIKO KEJADIAN STROKE DI RSUD UNDATA PALU TAHUN 2011 - Firdaus Koto (STRADA : Jurnal Ilmiah Kesehatan, 2013)
Stroke is a major problem faced by almost all over the world, both in developed and developing countries. Acute stroke that causes physical and mental disabilities as well as the high rate of sudden death, both in age and old age. This study aims to determine risk factors for stroke incidence in hospitals Undata Palu in 2011. This study uses an observational case-control approach. Case subjects were stroke patients in neurological diseases hospitals poly Undata Palu in 2011, and the control group were patients who had not suffered a stroke in neurological diseases hospitals poly Undata Palu in 2011. Sample of 51 cases and 102 controls with matching age. Selected a simple random sampling, and analyzed with odds ratios test. The results showed that hypertension (OR = 6.905 and CI = 3.265 to 14.605), hypercholesterolemia (OR = 8.140 and CI = 3.796 to 17.453), and heart disease (OR = 2.496 and CI = 1.246 to 5.000) are risk factors for stroke in hospitals Undata Palu in 2011.